Blue photoluminescence from active carboxyl adatoms on nanoporous anodic alumina films - Sam Yeon Cho; Kangmo Yeo; Jin Woo Kim; Jin Ho Kwak; Deok-Yong Cho; Jae Hyuck Jang; Sukmin Jeong; Yong Chan Choi; Sang Don Bu (Scientific Reports)
Abstract Nanoporous anodic alumina (nPAA) films formed on aluminum in lower aliphatic carboxylic acids exhibit blue self-coloring and characteristic properties such as photoluminescence (PL), electroluminescence, and electron spin resonance. The blue colors are seemingly originated from the adsorbed radicals incorporating into the oxide during the aluminum anodization. However, there is lack of reports revealing the detailed activation mechanism of the adatoms in the complexes. This study investigates the blue PL and its correlation with the atomic and electronic structures of the active aluminum surface using multiple theoretical and experimental methods. The results show that the concentration of carboxylates at the nPAA surface is highly correlated with the blue colorization and manifest that unpaired electrons in carbon (derived from the carboxylates) bridging two aluminum atoms at surface can play as an active source of the blue colorization. Therefore, it is suggested that controlling the adsorption of the carboxylate on the alumina membrane having large surface-to-volume ratio can be an efficient way to generate the blue light for the optoelectronic applications.